Evaluation of measurement uncertainty in creep-based determination of viscoelastic material functions of polypropylene - Kotnik, Urban (Strojniški vestnik, 2026)
Modern numerical models use time-dependent material parameters as input data to simulate the viscoelastic response of polymers. Reliable numerical predictions therefore depend on the accurate determination of these parameters. Understanding the measurement uncertainty associated with their identification is essential for assessing the expected range and reliability of the simulation results. Although creep-based uncertainty analyses have been reported for other materials, uncertainty evaluations for polymers that require the determination of multiple viscoelastic material functions remain scarce, with existing polymer studies primarily relying on relaxation tests. This study experimentally analyzes the viscoelastic behavior of polypropylene at 60 °C through tensile and shear creep tests based on extensional and rotational rheometry. The tensile, shear, and bulk compliance functions were determined together with their corresponding standard and expanded measurement uncertainties in accordance with the JCGM 100:2008 guideline. Type A uncertainties were found to dominate the overall uncertainty, with relative expanded uncertainties of approximately 3 percent for shear compliance and up to 25 percent for bulk compliance. The study identifies the main sources of uncertainty and proposes strategies for their reduction, including increasing the number of measurement repetitions and improving environmental control. Overall, a comprehensive uncertainty evaluation of the creep-based determination of viscoelastic material functions is presented, leading to more reliable input data for numerical simulations.
Keywords: creep tests; measurement uncertainty; merilna negotovost; polimeri; polimers; polipropilen; polypropylene; preizkusi lezenja; viscoelasticity; viskoelastičnost